Nonmemory Mike Kelley with Kelly Akashi, Meriem Bennani, Beatriz Cortez, Raúl de Nieves, Olivia Erlanger, Lauren Halsey and Max Hooper Schneider - Nayssan, Jay Ezra 1987- (Hauser & Wirth Publishers, 2023)
Curated by Jay Ezra Nayssan, ‘Nonmemory’ brings together seminal works by Mike Kelley and a group of seven contemporary artists – Kelly Akashi, Meriem Bennani, Beatriz Cortez, Raúl de Nieves, Olivia Erlanger, Lauren Halsey and Max Hooper Schneider – whose works all play with the role of memory as it posits our perceptions of space and place